2021
DOI: 10.1051/0004-6361/202038488
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength analysis of the X-ray spur and southeast of the Large Magellanic Cloud

Abstract: Aims. The giant H II region 30 Doradus (30 Dor) located in the eastern part of the Large Magellanic Cloud is one of the most active star-forming regions in the Local Group. Studies of H I data have revealed two large gas structures which must have collided with each other in the region around 30 Dor. In X-rays there is extended emission (~1 kpc) south of 30 Dor called the X-ray spur, which appears to be anticorrelated with the H I gas. We study the properties of the hot interstellar medium (ISM) in the X-ray s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
4
4
0
Order By: Relevance
“…We thus obtain a mean temperature of kT 1 = 0.22 keV with a standard deviation of σ kT 1 = 0.02 keV for the lower-temperature component and kT 2 = 0.74 keV and σ kT 2 = 0.10 keV for the higher-temperature component. These temperature values are consistent with the results of the analysis of XMM-Newton observations of southeastern parts of the LMC (regions around 30 Dor, in the X-ray spur, and west of them) by Knies et al (2021). As can be seen in Fig.…”
Section: Thermal Componentsupporting
confidence: 91%
See 2 more Smart Citations
“…We thus obtain a mean temperature of kT 1 = 0.22 keV with a standard deviation of σ kT 1 = 0.02 keV for the lower-temperature component and kT 2 = 0.74 keV and σ kT 2 = 0.10 keV for the higher-temperature component. These temperature values are consistent with the results of the analysis of XMM-Newton observations of southeastern parts of the LMC (regions around 30 Dor, in the X-ray spur, and west of them) by Knies et al (2021). As can be seen in Fig.…”
Section: Thermal Componentsupporting
confidence: 91%
“…The same stars, which have created the giant H ii region 30 Dor and the other H ii structures in its surroundings, are the likely sources of the hot interstellar plasma. This result corroborates nicely the scenario of the collision of large HI structures in the LMC for the origin of 30 Dor and the star-forming regions south of 30 Dor presented by Fukui et al (2017) and recently confirmed by Knies et al (2021) based on multi-wavelength study of the southeastern part of the LMC, in particular the X-ray spur. A large HI component, called the Lcomponent has encountered the HI component in the disk of the LMC (D-component) in the past, starting roughly at the position where 30 Dor is observed now.…”
Section: Foreground Absorption In the Lmcsupporting
confidence: 90%
See 1 more Smart Citation
“…It seems to emit higher energy X-rays than what is typically expected from interstellar plasma in galaxies. XMM-Newton studies of the X-ray spur have shown that the interstellar plasma has a higher temperature than in most other parts of the LMC, being as high as in the region around the Tarantula nebula in 30 Doradus and the super-star cluster RMC 136 inside it, which are heated by a large number of very massive stars and is located north of the X-ray spur [65]. In the X-ray spur, however, as the complementary multiwavelength analysis shows, there are no indications for the past and present existence of massive stars which might have caused the heating of the plasma at the position.…”
Section: X-ray Spur In the Lmcmentioning
confidence: 99%
“…We have recently analyzed the properties of the hot interstellar plasma in the entire interaction region using Xray data. The spectral analysis has shown that the plasma in the region around 30 Doradus and SGS LMC 2 has been heated by the young stars, while the region to the south must have been heated by the cloud collision (Knies et al 2021).…”
Section: Supergiant Shell Lmcmentioning
confidence: 99%